2023
DOI: 10.1039/d3ay00441d
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electrochemical glucose sensing of Co/Cu-MOF by hydroxyl adsorption induced reactive oxygen species

Abstract: Exploring the factors affecting the electrochemical catalytic signal of organic metal material sensor and analyzing the decisive steps of the glucose oxidation behavior is a challenging problem. Here, we designed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Practically, MOFs are reported to release metal ions and ligands in water media, concurrently experiencing structural reconstruction stimulated by electrochemical environment. Furthermore, it has been observed that MOFs undergo surface reconstruction to generate oxyhydroxides during glucose electrocatalytic oxidation. These phenomena raise two critical inquiries: first, the veritable source of catalytic activity governing glucose oxidation and, second, the extent to which this reconstruction transpires, whether it remains confined to the surface of MOFs or penetrates deeper as the reaction proceeds. Nevertheless, these aspects have not been explored in depth within the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…Practically, MOFs are reported to release metal ions and ligands in water media, concurrently experiencing structural reconstruction stimulated by electrochemical environment. Furthermore, it has been observed that MOFs undergo surface reconstruction to generate oxyhydroxides during glucose electrocatalytic oxidation. These phenomena raise two critical inquiries: first, the veritable source of catalytic activity governing glucose oxidation and, second, the extent to which this reconstruction transpires, whether it remains confined to the surface of MOFs or penetrates deeper as the reaction proceeds. Nevertheless, these aspects have not been explored in depth within the current literature.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Despite the significant advancements made with CPs/ MOFs, their application in glucose sensing has been hindered by the generally poor conductivity of the hybrid organic− inorganic polymers. 33,34 To address these limitations, innovative strategies have been implemented, including the integration of MOFs with conductive materials and performance improvement through the incorporation of transition metal ions, such as Ni, 35,36 Cu, 37,38 Ce, 39 Fe, 40 and Co, 41,42 which are known for their catalytic activity toward electrochemical sensing of glucose. This methodology not only diminishes the overpotential required for glucose oxidation but also enhances electron exchange through different mechanisms, thereby demonstrating the potential of CPs/MOFs in practical applications.…”
Section: Introductionmentioning
confidence: 99%